Stock Market Volatility Due to Cross-Listing of Tradable Assets - Keshari, Aditya; Gautam, Amit (Indian Journal of Finance, 2023)
Purpose : The study analyzed the return and volatility spillover among the Indian and overseas stock markets, namely Luxembourg, the United States, and the United Kingdom, where the assets are cross-listed. The increased worry of investors, regulators, and dealers about stock market volatility produced by worldwide integrated stock trading has focused on the symmetric and asymmetric volatility caused by the cross-listing of tradable assets that has damaged the domestic stock market. Methodology : The analysis for the study incorporated the longitudinal time series of daily closing prices from January 01, 2011, to December 31, 2021, of the sample indices taken from the Bloomberg terminal. The study used GARCH, EGARCH, and PARCH models to analyze the return and volatility spillover among the Indian and cross-listed stock markets. Findings : The findings indicated that prior index return volatility was significant and impacted current index return volatility. The findings also suggested that volatility exhibited asymmetric behavior, with positive shocks to volatility having different impacts than adverse shocks. The Luxembourg Stock Exchange was negligible in all models, implying it is exogenous. Practical Implications : It was suggested that investors use information from another market to forecast the behavior of one market. The current analysis supported this assumption by demonstrating the market dominance of the United States. By focusing on market activity in the United States, preventative measures could be taken to minimize worldwide shocks. Originality : The present study incorporated the impact of cross-listing of tradable assets and volatility, which was yet to be investigated earlier despite cross-listing being an essential aspect of the spillover effect.